Math Learning with Realistic Mathematics Education Approach (RME) Based On Open Source - Ended to Improve Mathematic Communication (Universitas Negeri Semarang, 2018)
This study aims to determine the feasibility and effectiveness of the application of learning using social arithmetic teaching books by Realistic Mathematics Education (RME) approach based on Open-Ended problem. The research design used in this research is Research and Development with Plomp model. Subjects in this study were students of class VIII SMP Askhabul Kahfi academic year 2017 / 2018. Design implementation is using Posttest Only Control-Group Design. The analysis technique used in the form of analysis of expert validation results and effectiveness test. Post test results on the class performed by the action are compared to the non-action class to ensure, it is done by (1) Complete Test, (2) Different Test, and (3) Simple Linear Regression Test. The results of this study obtained data that (a) the average value of evaluation of classroom communication skills using mathematics learning tools 73.42 (Î¼> 70) and classical mastery of 76.6% (Ï€> 75%); (b) the average rate of classes using the application of mathematics learning tools with RME approach based on open-ended problem (73.42) is greater than the class that does not use the application of mathematics learning tool with RME approach based on open-ended problem (64.57) and (c) from the regression test obtained tcount = 2.012, tcount (2.012)> ttable (1.99834). Based on the results of research and discussion, obtained the conclusion that (1) Arithmetic learning devices with RME approach developed valid is used based on the expert judgment. According to the results of small large class test, and (2) Arithmetic learning tools with RME approach developed effectively.